Nutrient enhancement of flooded soil by symbiotic soil fungi - Nor Hazwani, Aziz (2021)
Flooding was classified as one of the major threats to Asia and the Pacific region, and in fact, to numerous parts of the world. While the impacts are not the deadliest, this sort of common catastrophes exhibited a sharp increment in number and was identified as the most frequent event. The worsening effect of flooding is that it left behind the barren land where the soil could not support plant growth due to the leaching of nutrients and the losses of beneficial living microorganisms that facilitate the uptake of water and nutrients. Therefore, a biological method was proposed to restore soil fertility by exploiting the ability of soil fungi in promoting the uptake of nutrients from the soil by forming a symbiotic interaction with the host plants (Allium cepa). In light of this, this current study attempts to screen the factors affecting the recovery of flooded soil and optimize the condition for optimum recovery of nutrients by soil fungi. Also, this study aimed to isolate and identify the soil fungi population from the treated soil and to perform the kinetic study of nutrient uptake by soil fungi through the Michaelis-Menten model, as well as to determine the mechanism of nutrient released by soil fungi. In this current study, the fertile soil containing naturally occurring fungi was collected from fertile land, and flooded soil was simulated under the greenhouse. The host plant's growth was preliminarily studied in three soil conditions, namely fertile soil, flooded soil, and the treated soil (a mixture of fertile and flooded soil). The concentration of nutrients (nitrogen, phosphorus, and potassium) was measured by using a spectrophotometer. The factors affecting the soil recovery were selected and screened by fractional factorial design, while optimization of flooded soil recovery was conducted by employing response surface methodology. Soil fungi were isolated and identified by the Biolog Gen III MicroPlate Identification system. A kinetic study was carried out, and the enzymatic assay was performed to investigate the mechanism of nutrients released by soil fungi. The screening of factors affecting the soil recovery presented that four factors, including water content, light supply, soil depth, and soil ratio to have significant effects on the recovery of nutrients. Soil water content at 28 mL and soil depth of 5 cm was found to be optimum in increasing the concentration of nutrients in the soil. At this condition, the nutrient uptake by soil fungi was said to be at their maximum rate, where the concentration of nutrients was doubled from the recorded initial concentration. The kinetic constant of Vmax and Km obtained were varied for nitrogen, phosphorus, and potassium and were reported as 6.28 mg/L.d and 82.17 mg/L for nitrogen, 9.80 mg/L, and 60.96 mg/L.d for phosphorus and 0.07 mg/L and 4.55 mg/L.d for potassium, respectively. Two fungi species were identified with a probability of more than 90%, namely Aspergillus aculeatus and Paecilomyces lilacinus. The finding of this study suggests that inoculating flooded soil with fertile soil containing beneficial soil fungi could significantly increase the nutrient concentration and hence could reduce the application of chemical-based fertilizers in order to achieve sustainable farming.